Dynamic analysis of the train-bridge system considering the non-linear behaviour of the track-deck interface. (1st October 2020) - Ticona Melo, L.R.; Malveiro, J.; Ribeiro, D.; Calçada, R.; Bittencourt, T.
Highlights: Train-track-bridge interaction problem with non-linear behavior of track-deck interface. Track-deck interface behavior is more influenced by temperature than traffic loads. Plastic incursions at track-deck interface were detected under deck temperature variations. Extension of plastic regions is sensitive to variations of the support's horizontal stiffness. Elastic behavior in short spans and plastic behavior in medium/large span bridges. Abstract: This article presents an efficient computational methodology for solving the train-track-bridge interaction problem, including track irregularities and considering the non-linear behaviour of the track-deck interface. One of the novelties of the work is the proposal of a specific finite element used to model the track-deck interface, based on an assembly of a friction contact element and a non-linear spring, which is generally not used in non-linear dynamic problems. This element automatically performs changes in the longitudinal resistance of the track, according to the positions of the traffic loads, and takes into account the loading history. The dynamic analyses are performed based on an iterative methodology implemented in AIVE software, which takes advantage of the advanced modeling tools of Abaqus software controlled on Matlab. This software ensures flexibility in the selection of the methods for solving the dynamic problem and allows the incorporation of non-linearities in the vehicle and bridge models, including their interfaces. A parametric study was performed in order to demonstrate the importance of including the non-linear behaviour at the track-deck interface in the evaluation of the dynamic responses of the bridge and vehicle subsystems, under different scenarios of deck temperature, horizontal stiffness of the supports and deck cross-sections. The results show that the responses of the track-deck interface are more influenced by the effects of temperature variations than by the effects of vertical traffic loads, particularly for medium and large span bridges. Significant plastic incursions were detected at the track-deck interface under realistic temperature scenarios, particularly on the side of the mobile support. Under vertical traffic loads, the extension of the regions with plastic behaviour proved to be sensitive to variations in the horizontal stiffness of the support. Additionally, another important achievement of this study was the evaluation of the plastic incursions at the track-deck interface for different bridges typologies. Relevant incursions were detected for medium and large span bridges, where the extension of these regions can reach 25–55% of the bridge span, otherwise, for short span bridges, practically no significant plasticized regions were identified. Non-linear incursions on the track-deck interface cause an overall reduction of the track-bridge stiffness, leading to an increase of the vertical movements of the bridge, and, inherently, of the vehicle's dynamic responses. The evaluation of the extension of the ballast plastic regions for the different analysis scenarios, which is still a topic shortly addressed in the bibliography, will be particularly useful for upgrading the existing methods for assessment of the dynamic behavior of railway bridges.